A dynamic network discovery and selection method for heterogeneous wireless networks. (22nd July 2009) - Siddiqui, Farhan; Zeadally, Sherali; El-Sayed, Hesham; Chilamkurti, Naveen
Next generation communication systems aim at providing ubiquitous network access by integrating a wide-range of wireless technologies. The availability of various access networks requires a mobile device to be capable of selecting the best access network with minimum user intervention. We present a design architecture that efficiently discovers available wireless networks, and implements automatic network selection based on several factors such as the conditions of accessible networks, requirements of active applications, and preferences of the mobile user. We also present a case study to demonstrate the operation of the proposed prototype architecture in an actual heterogeneous network testbed.